2021
DOI: 10.3389/fmicb.2021.654345
|View full text |Cite
|
Sign up to set email alerts
|

A Hyperthermophilic Argonaute From Ferroglobus placidus With Specificity on Guide Binding Pattern

Abstract: Argonaute proteins (Agos) from thermophilic archaea are involved in several important processes, such as host defense and DNA replication. The catalytic mechanism of Ago from different microbes with great diversity and genome editing potential is attracting increasing attention. Here, we describe an Argonaute from hyperthermophilic Ferroglobus placidus (FpAgo), with a typical DNA-guided DNA endonuclease activity but adopted with only a short guide 15–20 nt length rather than a broad guide selectivity for repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The optimal NaCl concentration for 5′‐P DNA guide was from 0 to 250 mM, while the optimal range for 5′‐OH DNA guide was only from 100 to 150 mM (Figure 2b,h). Recent studies have revealed that divalent metal ions such as the most common Mn 2+ is essential for Ago activity, while some pAgos also show activities with Mg 2+ or Co 2+ (Chong et al, 2019; Guo et al, 2021). Therefore, six divalent metal ions including Mg 2+ , Ca 2+ , Mn 2+ , Co 2+ , Cu 2+ , and Zn 2+ were tested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal NaCl concentration for 5′‐P DNA guide was from 0 to 250 mM, while the optimal range for 5′‐OH DNA guide was only from 100 to 150 mM (Figure 2b,h). Recent studies have revealed that divalent metal ions such as the most common Mn 2+ is essential for Ago activity, while some pAgos also show activities with Mg 2+ or Co 2+ (Chong et al, 2019; Guo et al, 2021). Therefore, six divalent metal ions including Mg 2+ , Ca 2+ , Mn 2+ , Co 2+ , Cu 2+ , and Zn 2+ were tested.…”
Section: Resultsmentioning
confidence: 99%
“…The target RNA cleavage of Tt Ago has been almost abolished by a single mismatch surrounding the cleavage site (Wang et al, 2008), while its target DNA cleavage was affected most by the mismatches at 3′‐supplementary region (Hunt et al, 2018; Song et al, 2020). For Km Ago, Cp Ago, Ib Ago, and Fp Ago, mismatches near the cleavage site (guide positions g10–g11) or the 3′‐supplementary region (guide positions g13–g15) were less tolerated (Cao et al, 2019; Guo et al, 2021; Kropocheva et al, 2021). To investigate the effects of guide‐target mismatches on the activity of Ttr Ago, the mismatches at positions 2–16 of the guide DNA was introduced and assayed accordingly (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Argonautes of bacteria and archaea discri-minate guides by the nitrogenous base of the 5'-terminal nucleotide: RsAgo from the bacterium Rhodobacter sphaeroides binds guides containing uracil at the 5' end, TtAgo from the bacterium Thermus thermophilus ‒cytosine, FpAgo from the archaea Ferroglobus placidus ‒guanine, MjAgo from archaea Methanocaldococcus jannaschii –purines. At the same time, other studied prokaryotic Argonautes do not show specificity for the 5'-terminal nucleotide ( Table 1 ) [ 101 103 , 122 , 124 , 125 , 130 , 141 , 142 , 146 , 159 ]. The corresponding unpaired nucleotide of the target chain can be specifically recognized in a separate pocket of the PIWI domain (G for TtAgo, A for RsAgo) [ 145 , 158 ].…”
Section: Argonaute Proteins—another Group Of Programmable Nucleasesmentioning
confidence: 92%
“…Eukaryotic Argonaute proteins (eAgos) are a core of eukaryotic RNA interference (RNAi) machinery [ 1 , 2 ], which use RNA guides to recognize and cleave complementary RNA targets. Prokaryotic Argonautes (pAgos) are found in bacteria and archaea [ 3 , 4 , 5 , 6 ], such as TtAgo from Thermus thermophilus [ 7 ], PfAgo from Pyrococcus furiosus [ 8 ], and MjAgo from Methanocaldococcus jannaschii [ 9 ]. These pAgos prefer to cleave DNA in vitro and protect cells from foreign genetic elements in vivo [ 4 ].…”
Section: Introductionmentioning
confidence: 99%